Zimbabwe's emergency response to COVID-19: Enhancing access and accelerating COVID-19 testing as the first line of defense against the COVID-19 pandemic - Gudza-Mugabe, Muchaneta; Sithole, Kenny; Sisya, Lucia; Zimuto, Sibongile; Charimari, Lincoln S.; Chimusoro, Anderson; Simbi, Raiva; Gasasira, Alex (Frontiers in Public Health, 2022)
The COVID-19 virus spreads rapidly causing outbreaks which grow exponentially within a short period of time before interventions are sought and effectively implemented. Testing is part of the first line of defense against COVID-19, playing a critical role in early identification, isolation of cases to slow transmission, provision of targeted care to those affected, and protection of health system operations. Laboratory tests for COVID-19 based on Nucleic Acid Amplification Techniques were rapidly developed in the early days of the pandemic, but such tests typically require sophisticated laboratory infrastructure and skilled staff. To date, hundreds of millions of COVID-19 tests have been performed globally, but the demand for timely access, accurate testing, and geographic availability of diagnostics remains a challenge in most countries. In March 2020 Zimbabwe experienced the first case of COVID-19 which saw the country experiencing exponential growth in infection rates spreading across the country and a high demand for testing. One National laboratory was set to test all the country`s COVID-19 suspect cases building pressure on human and financial resources. Staff burn out, longer turnaround times of more than 48 hours were experienced and results would be released late with no clinical value. The gene Xpert testing labs were out of stock of SARs-CoV-2 cartridges for a long time leading to work overload at few testing sites contributing to very long turnaround times. On September 11, WHO released the interim guidance to use antigen rapid diagnostic test (Ag-RDT) as a diagnostic test. The Zimbabwe laboratory pillar quickly adopted it and made plans for its implementation. The National microbiology reference laboratory (NMRL) verified the two emergency listed kits, the Pan Bio and the Standard Q and they met the WHO minimum performance of ≥97% specificity and ≥80% sensitivity. Training on use of Ag-RDT diagnostic testing was commenced and testing was decentralised to all the 10 provinces, from 1 testing central laboratory to more than 1000 testing centers. Result turnaround times were improved to same day and accessibility to testing enhanced. Decentralisation of diagnostic testing leveraging on existing human resources became a game changer to improving COVID-19 containment measures.